Mediating Xenophobia in Africa
XXVIII, 394 p. 30 illus., 26 illus. in color.
Keywords: “Communal conflict continually reminds us why humans seek communal solidarity and should fear it. As this volume’s authors demonstrate, the names and terms we use carry moral value about deservingness, about hospitality, and about rights to space and resources. This book offers distinct insights that explain the dynamic dangers of exclusion. The book deserves particular credit for deploying a remarkable collection of scholars and practitioners to surface these themes. While many will not yet be known to the global academy, their contributions suggest they should be.” -- Loren B. Landau, Professor, University of Oxford, UK and University of the Witwatersrand, South Africa “Moyo and Mpofu have successfully assembled a stellar group of academics to explore the complex and indeed opaque subject of xenophobia. The result is a brilliant and enlightening volume that expands the canvas of perspectives and advances frontiers of knowledge. I have nothing but praise for this important volume.” --Sabelo J. Ndlovu-Gatsheni, Professor and Chair of Epistemologies of the Global South, University of Bayreuth, Germany This book brings together contributions that analyse different ways in which migration and xenophobia have been mediated in both mainstream and social media in Africa and the meanings of these different mediation practices across the continent. It is premised on the assumption that the media play an important role in mediating the complex intersection between migration, identity, belonging, and xenophobia (or what others have called Afrophobia), through framing stories in ways that either buttress stereotyping and Othering, or challenge the perceptions and representations that fuel the violence inflicted on so-called foreign nationals. The book deals with different expressions of xenophobic violence, including both physical and emotional violence, that target the foreign Other in different African countries. Dumisani Moyo is Associate Professor of Communication and Vice Dean, Academic at the University of Johannesburg, South Africa. Shepherd Mpofu (PhD) is Senior Lecturer at the University of Limpopo, South Africa.